Anti leishmanial Activity of Methanolic extract of Juniperus excelsa berries and Acacia nilotica - S. Al-Bayati, Nuha; A. Anwar, Sheelan; I. Mahmood, Omaima (Tikrit Journal of Pharmaceutical Sciences, 2023)
This study was conducted from December 2012 to May 2013. Samples were taken from the lesions of patients attending Tikrit Teaching Hospital and diagnosed clinically by professional doctors in dermatological department in the hospital clinically identified as Leishmania sp. according to lesion characteristics form. Parasites Isolates were harvested at stationary phase of growth injected intradermaly of 40 BALB/c mice for each plant. There were significant differences (P<0.001) in numbers of parasite cells in most concentrations used for methanolic extract of Juniperus excelsa berries compared with the control group without agent, and the statistically analysis showed that there were no significant differences (P>0.05) in the numbers of parasite cells in all concentrations used for methanolic extract of Acacia nilotica compared with the control group without agent. Also there were significant decrease (P<0.01) in number of parasite cells in control group treated with Pentostam compared with control group without agent